Fotossíntese e condutância estomática de tomate SM-16 e Mariana cultivados com diferentes tipos de cobertura do solo - Batista, Thaíza Mabelle de Vasconcelos (Universidade Federal Rural do Semi-Árido, 2011)
The plastic films of polyethylene have been widely used for mulching, these treatments have benefits such as increased water conservation, reduction of losses by leaching, increased soil moisture, protection of the fruits, etc. The aim of this study was to evaluate the photosynthesis and stomatal conductance of the hybrids Mariana and SM-16 cultivated with or without mulching. The experimental design was a complete randomizes blocks with four replications. Treatments were arranged in split plots with the plots represented by cropping systems (uncover soil, black polyethylene, gray polyethylene, white polyethylene, and black polypropylene) and the sub-plot constituided by the hybrids ('Mariana' and 'SM-16') or plant sampling times (28, 56 and 84 days after transplanting). The hybrid SM-16 showed an average of photosynthesis and stomatal conductance found in the upper Mariana, but the latter showed greater efficiency in water use. Mulching treatments did not affect photosynthesis and stomatal conductance
Keywords: Lycopersicon esculentum Mill; Mulching; Atividade fotossintética; Lycopersicon esculentum Mill; Photosynthetic activity; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA